Observation and analysis of factors influencing performance of the Chinese female biathalon team in shooting training - Liu, F.; Duan, L.; Yao, H. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this research was to analyze and estimate the results of heart rate, percentage of hits and nervous level with the expectation of developing an appropriate shooting strategy for each athlete. Methods Six athletes from the National Women`s Biathlon Team who were for the Winter Olympic Games in Italy 2006, were recruited to take part in the study. Artificial records in a shooting range and time records using Polar heart rate monitors were used to collect the correlated indexes in shooting training. EEG (Electroencephalography) and BEAM (Brain Electrical Activity Mapping) were used to measure of nerve function level in the laboratory. Results / Conclusions The outstanding Biathlon athletes in China can be divided into two groups: that is, senior athletes and young athletes according to their shooting features. There were many factors influencing the shooting performance of these athletes, who also demonstrated individual differences. The heart-blood function level and the nerve function level were major factors influencing performances. The heart-blood function level, especially the variation of heart rate also influences the shooting result. However, reducing the heart rate will not always increase the percentage of effective hits. Similarly, nerve function level, especially its stability will also affect shooting outcomes and senior athletes were found to be more skilled than their younger counterparts in the regulation and stability of nerve function.